AWS Machine Learning: Building an Expense Tracker Using Amazon Textract. - Rivas, Carlos (linkedin.com, 2021)
Certified AWS Solutions Architect Carols Rivas leads this project-based course on Textract, the Amazon OCR tool for parsing text out of images.